Lectures on the philosophy of religion - Hegel, Georg Wilhelm Friedrich (Oxford University Press,Clarendon Press, 2007)
Hegel's lectures have had as great a historical impact as the works he himself published. Important elements of his system are elaborated only in the lectures, especially those given in Berlin during the last decade of his life. The original editors conflated materials from different sources and dates, obscuring the development and logic of Hegel's thought. The Hegel Lectures series is based on a selection of extant and recently discovered transcripts and manuscripts. The original lecture series are reconstructed so that the structure of Hegel's argument can be followed. Each volume presents an accurate new translation accompanied by an editorial introduction and annotations on the text, which make possible the identification of Hegel's many allusions and sources